About creation of a techological tomograph using the ELIAS accelerator - Arkatov, Yu.M.; Afanas’yev, S.N.; Sorokin, P.V. (Вопросы атомной науки и техники, 2002)
Estimates were made for the possibility of creating a technological tomograph based on the registration of Compton scattering of photons through the use of the Van de Graaff accelerator (ELIAS) at NSC KIPT. The GEANT3 package was used to simulate the process of production of a sharply directed bremsstrahlung beam, to define the converter thickness, and to determine the angular distribution and energy spectrum of photons. The computation of counting rate for the tomograph’s detector has shown that for materials of a density up to 3 g/cm3 the counting rate can reach 2600 counts/sec, this being quite sufficient for tomographs of this type.